2020
DOI: 10.1021/acsapm.0c00239
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Sensing of Paracetamol Using Iron Oxide Encapsulated in Chitosan-Grafted-Polyaniline

Abstract: Potentiometric sensing of paracetamol over molecularly engineered and chemically responsive α-Fe2O3 encapsulated chitosan grafted polyaniline (α-Fe2O3-en-CHIT-g-PANI) coated ITO glass electrode has been demonstrated. The effect of molecular engineering on the structure, morphology and physical properties of α-Fe2O3-en-CHIT-g-PANI was investigated by Fourier transform infrared spectrometer (FT-IR), X-ray diffraction (XRD), scanning electron microscope (SEM) and two probe methods. The observed result suggests th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Furthermore, the synergism of electrical conductivity with functionality and responsiveness due to encapsulation of metal oxides, grafting biopolymer has significantly improved their applications in the sensing sciences in terms of sensitivity, selectivity, and sensing mechanism [ 11 ]. Shukla et al reported electrically conducting ternary bio nano composite with catalytical nature towards sensing paracetamol after measuring the potential generated after catalytical surface oxidation in the presence of iron oxide [ 12 ]. However, the presence of biocompatibility makes conducting polymer suitable for a biochemical reaction for the fabrication of biomedical devices and biosensors.…”
Section: Macromolecular Theory and Historical Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the synergism of electrical conductivity with functionality and responsiveness due to encapsulation of metal oxides, grafting biopolymer has significantly improved their applications in the sensing sciences in terms of sensitivity, selectivity, and sensing mechanism [ 11 ]. Shukla et al reported electrically conducting ternary bio nano composite with catalytical nature towards sensing paracetamol after measuring the potential generated after catalytical surface oxidation in the presence of iron oxide [ 12 ]. However, the presence of biocompatibility makes conducting polymer suitable for a biochemical reaction for the fabrication of biomedical devices and biosensors.…”
Section: Macromolecular Theory and Historical Advancesmentioning
confidence: 99%
“…This catalytic behavior integrated electrically conducting bio composite was reported suitable for potentiometric sensing of residual paracetamol sensing in hospital waste water and mechanism lying in paracetamol sensing is illustrated in Fig. 4 along with brief finding [ 12 ].
Fig.
…”
Section: Overview On Macromolecules As Sensing Materialsmentioning
confidence: 99%
“…Most of these pharmaceutical products often end up in the aquatic environment as micropollutants. Because of their omnipresent nature, they are practically detected in every environmental matrix including groundwater, surface water, effluents from wastewater plants, and sludge. , Currently, paracetamol (PCT), the most widely consumed nonprescribed medicine (30 000–35 000 tons annually), has emerged as a pollutant of grave concern. It is a multifunctional antipyretic and analgesic drug used to appease pain, lessen body temperature, and for neuralgia .…”
Section: Introductionmentioning
confidence: 99%
“…Paracetamol (PA), one of the frequently used anti-inammatory and antipyretic agents, has been extensively adopted to relieve migraine, headache, osteoarthritis pain and postoperative pain in the clinic. 1,2 Nonetheless, long-term and excess PA application can result in toxic metabolite accumulation, thereby damaging the liver or kidneys. 3 As a result, it is of much importance to develop a simple, sensitive and accurate quantitative tool for PA analysis, which can be applied in quality control and clinical diagnosis to analyze PA-containing drugs.…”
Section: Introductionmentioning
confidence: 99%